PENYAJIAN LAPORAN KEUANGAN ENTITAS BERORIENTASI NONLABA BERDASARKAN ISAK 35 PADA MASJID BAITUL HAADI - Diviana, Sukma; Putra Ananto, Rangga; Andriani, Wiwik; Putra, Roni; Yentifa, Armel; Zahara; Siswanto, Azi (Jurusan Akuntansi Politeknik Negeri Padang, 2020)
Mosque is an entity that aims not for profit (non-profit entity), so that financial accountability becomes an important aspect for mosques. Good accountability can be realized by presenting the mosque's financial reports in accordance with generally accepted accounting standards. The standard governing the financial reporting of non-profit entities is the Interpretation of Financial Accounting Standards No. 35 (ISAK 35). By implementing ISAK 35 in the presentation of mosque financial reports, interested parties will be able to assess the financial performance of the mosque. The object of this research is Mosque Baitul Haadi. Data were collected through a series of interviews and observations. Until now, Mosque Baitul Haadi only presented financial reports as far as cash in and cash out. This study aims to compile the financial statements of Mosque Baitul Haadi based on ISAK 35 using Microsoft Excel application tools. The financial statements that will be produced are the statements of financial position, comprehensive income statements, cash flow statements and notes to financial reports.